A new index to quantify dried soil layers in water-limited ecosystems: A case study on the Chinese Loess Plateau - Wang, Yunqiang; Shao, Ming'an; Zhu, Yuanjun; Sun, Hui; Fang, Linchuan (Geoderma, 2018)
Soil-water deficit causes dried soil layers (DSLs) worldwide in regions covered by deep soils including soils typically found on the Chinese Loess Plateau. Traditional indices for grading DSLs have a variety of units which may lead to inconsistent conclusions and comparisons. A new index to quantify DSLs is needed for studies in soil science, ecology, and hydrology. We proposed a new quantitative index (QI) to quantify the severity of DSLs and evaluated its utility using field data collected to a depth of 1800 cm at four sites. We then determined the spatial-temporal variation and influencing factors of the QI across the entire Loess Plateau based on data sets for 382 sites in 2008. The use of the QI decreased the influence of sampling depth and soil texture on DSL evaluation, and the inconsistency of the traditional indices in quantifying DSL severity. The comparison of traditional DSL indices and QI within the 0–1800 cm layer further verified that QI could capture the vertical changes of DSLs extent among different locations. The QIs ranged from 0.11 to 0.95 at a regional scale, with moderate variation (CV = 38%) throughout the Loess Plateau. Correlation, principal component, and minimum data set analyses showed that altitude, precipitation, normalized difference vegetation index, evaporation, land use, plant age and saturated soil water content explained, in descending order, most of the QI regional variation. A distributional map of QIs developed by using regression kriging indicated that most of the regions on the Loess Plateau had severe DSLs, especially in western part of the plateau. Land-use management (including plant age) most effectively mediated DSLs at different spatial and temporal scales. The proposed QI is expected to be widely used to characterise the overall condition of a DSL. The information on QI variation at a regional scale will be useful for reclaiming DSLs using land and vegetational management in regions around the world with deep soils. •The new index overcomes the impacts of soil texture and sampling depth on dried soil layers grading.•The data in 0–18 m soil profile showed the new index could capture vertical changes in the extent of dried soil layers.•Most of the regions on the Chinese Loess Plateau were characterised by severe dried soil layers.•The new index was influenced by seven factors selected in minimum data set.•Land use and plant age were identified as key factors for mediating dried soil layers.